A biomechanical analysis of successful and unsuccessful quadruple Toe Loop figure skating jumps - King, D. (Medicine & Science in Sports & Exercise, 2002)
Introduction: To be internationally competitive, male figure skaters must be able to complete quadruple revolution jumps consistently and safely. Research on double and triple Axels suggests that angular velocity and moment of inertia, not jump height, are two of the most critical variables for the successful completion of that jump (Aleshinsky, 1988). Angular momentum at take-off remains relatively constant from jump to jump (Aleshinsky, 1988; Albert and Miller, 1996). However, no research to date is available on 'quad' jumps. Thus, the purpose of this study was to investigate the characteristics of successful and unsuccessful quadruple toe loop jumps. Methods: Data were collected during the 2000 State Farm Figure Skating Championships. Four video cameras (120 fps) were used with a pan and tilt camera system (Peak Performance Technologies, Inc.) to record the quadruple jumps performed at Nationals. Two cameras each were placed on both sides of the rink and were gen-locked. A calibration was done using survey poles placed on the ice surface. Data were manually digitized and then filtered using a low pass filter (6 Hz cutoff). Three dimensional coordinates were calculated using the Peak Motus pan and tilt procedure. These data were analyzed using software written in LabView (National Instruments, Inc.). In total, four skaters attempted quad toe loops, from which five successful jumps and four unsuccessful jumps (the skaters fell) were analyzed. Due to the small number of 'quads' analyzed, only descriptive statistics were performed. Results: In both successful and unsuccessful quad toe loops, the skaters completed on average 3.1 revolutions in the air. The successful jumps were on average 88 degrees further around (preRot) at take-off as compared to the unsuccessful jumps. At landing, they were 102 degrees closer to completing the last revolution (LandRot) as compared to the unsuccessful jumps. The average angular velocities were slightly greater for successful jumps. The skaters' moments of inertia about a longitudinal axis through the trunk were 33% smaller at take-off, and their angular momenta (Hto) were 16% larger. Approach velocity (Hvapp), vertical velocity at take-off (Vvto), and flight times (T) were similar for both the unsuccessful and successful jumps.